Ventilatory support in the intensive care unit. Issue 10 (October 2016) - Hughes, Martin; Strachan, Laura
Abstract: This article focuses on a classification of modes of mechanical ventilation, the indications for and complications of invasive and non-invasive mechanical ventilation and the recent evidence on adjuncts to mechanical ventilation.